A note on semialgebraically proper maps - Dae Heui Park (Український математичний журнал, 2014)
We prove that a semialgebraic map is semialgebraically proper if and only if it is proper. As an application of this assertion, we compare the semialgebraically proper actions with proper actions in a sense of Palais.